AXIOLOGICAL REFRACTION OF RATIONALITY AS RELEVANT ASPECT OF THE PROJECTION OF BECOMING OF THE MODERN POSTNONCLASSICAL SCIENTIFIC PARADIGM - S.Y. NIKOLAEV (Advanced Engineering Research)
In this article attempt to interpret the phenomenon of cognitive world through axiological prism of universalies of culture is undertaken. Is explicized categorial sense of criterion of the rationality, being the common for all stages of development of the science, capable to act as the basis of methodological reconstruction of unity of scientific knowledge. Are analyzed socioculture preconditions of becoming of a modern postnonclassical scientific paradigm in system of culture.